Overweight modifies the longitudinal association between uric acid and some components of the metabolic syndrome: The Tromsø Study - Norvik, Jon Viljar; Storhaug, Hilde-Merete; Ytrehus, Kirsti; Jenssen, Trond Geir; Zykova, Svetlana; Eriksen, Bjørn Odvar; Solbu, Marit Dahl (BMC Cardiovascular Disorders, 2016)
Published version. Source at http://dx.doi.org/10.1186/s12872-016-0265-8 Background: Elevated uric acid (UA) is associated with the presence of the metabolic syndrome (MetS). In a prospective cohort study, we assessed whether baseline and longitudinal change in UA were risk factors for development of MetS and its individual components. Methods: We included 3087 women and 2996 men who had UA measured in the population based Tromsø Study 1994–95. The participants were stratified according to body mass index (BMI). Endpoints were MetS and each component of the syndrome after 7 years, according to the revised National Cholesterol Education Program’s Adult Treatment Panel III (NCEP-ATP III) definition. Results: Multiple logistic regression analyses showed that higher baseline UA was associated with higher odds of developing elevated blood pressure in overweight subjects (BMI ≥ 25 kg/m2, odds ratio [OR] per 59 μmol/L UA increase 1.44, 95 % confidence interval [CI] = 1.17–1.77, P = 0.001), but not in normal-weight subjects (BMI < 25 kg/m2, P for interaction = 0.04). Overweight also modified the association between baseline UA and the development of elevated fasting glucose (P for interaction = 0.01). UA was a predictor of MetS in all subjects (OR per 59 μmol/L UA increase 1.29, 95 % CI 1.18–1.41, P < 0.001). Furthermore, longitudinal UA change was independently associated with the development of MetS in all subjects (OR per 59 μmol/L UA increase over 7 years 1.28, 95 % CI 1.16–1.42, P < 0.001). Conclusion: Increased levels of baseline UA independently predicted development of elevated blood pressure and higher fasting glycemia in the overweight, but not the normal-weight subjects. Baseline UA and longitudinal increase in UA over 7 years was associated with the development of MetS in all subjects. Whether increased UA should be treated differently in normal-weight and overweight persons needs further study.